THE EFFECT OF INTEGRATED THEMATIC TEACHING MATERIALS USING THE CONTEXTUAL TEACHING AND LEARNING APPROACH TO THE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Dewi Lusiana; Taufina (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine the effect of integrated thematic teaching materials using a Contextual Teaching and Learning (CTL) approach for elementary school students. This research was an experimental study using a post only test research design. The procedure of this study consisted of a prerequisite test and a hypothesis test. The prerequisite test consisted of tests of normality and homogeneity and the hypothesis test consisted of the T test. The calculation results found that the t count of 12.2023 and t table 11.66895 at the level of significance α = 0.05 because t count waslarger than t table then Ho was rejected , and Ha was accepted. So it can be concluded that there was a significant influence on the use of thematic teaching materials using CTL on the learning outcomes of elementary school students. The implication of this research was that it can be used as a reference in the learning process in elementary schools.